2013
DOI: 10.1016/b978-0-12-417164-0.00024-0
|View full text |Cite
|
Sign up to set email alerts
|

Ice Recovery Assay for Detection of Golgi-Derived Microtubules

Abstract: Proper organization of the microtubule cytoskeleton is essential for many cellular processes including maintenance of Golgi organization and cell polarity. Traditionally, the centrosome is considered to be the major microtubule organizing center (MTOC) of the cell; however, microtubule nucleation can also occur through centrosome-independent mechanisms. Recently, the Golgi has been described as an additional, centrosome-independent, MTOC with distinct cellular functions. Golgi-derived microtubules contribute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Unfortunately, this proved to be impossible owing to the severe fragmentation of the Golgi apparatus occurring when MTs are depolymerized in this cell line. However, this line of analysis was possible in RPE1 cells which maintain a relatively organized Golgi apparatus even in the total absence of MTs [18] . After 25 seconds of MT regrowth, Cep192 siRNA treated RPE1 Centrin-GFP cells displayed a 2.6-fold relative increase in the number of non-centrosomal MTs (neither end attached to the centrosome) with the majority of these having one end clearly associated with the Golgi apparatus ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, this proved to be impossible owing to the severe fragmentation of the Golgi apparatus occurring when MTs are depolymerized in this cell line. However, this line of analysis was possible in RPE1 cells which maintain a relatively organized Golgi apparatus even in the total absence of MTs [18] . After 25 seconds of MT regrowth, Cep192 siRNA treated RPE1 Centrin-GFP cells displayed a 2.6-fold relative increase in the number of non-centrosomal MTs (neither end attached to the centrosome) with the majority of these having one end clearly associated with the Golgi apparatus ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To quantify extra-centrosomal MT regrowth, RPE1 cells were plated on coverslips, depleted of siRNA for 72 hours and processed as described elsewhere, allowing 25 seconds of regrowth in 21°C media and 2 minutes in extraction buffer before fixation in methanol and immunostaining [18] , [19] . Extra-centrosomal MTs were counted by hand using ImageJ software.…”
Section: Methodsmentioning
confidence: 99%
“…The response of MTs to changes in the activity of regulators is influenced by the concentration of free assembly–competent tubulin, the concentration of MT ends, the nucleation capacity of the centrosome ( Zhou et al ., 2002 ), and possibly other regions of cellular MT assembly ( Chabin-Brion et al ., 2001 ; Grimaldi et al ., 2013 ). In live mammalian cells, it is extremely difficult, if not impossible, to measure the total number of MTs and thus the concentration of free MT ends.…”
Section: Discussionmentioning
confidence: 99%
“…Microtubules grow mainly from the centrosome. Relatively recently it was found that Golgi membranes are also directly involved in the nucleation and organization of cellular microtubules [72,73]. By gliding along micro tubules growing from them, Golgi membranes can con centrate in a sufficiently compact area within the cell even in the absence of a centrosome, e.g.…”
mentioning
confidence: 99%
“…Microtubule nucleation at the Golgi membranes can be reproduced in vitro using isolat ed membranes and purified tubulin: under suitable condi tions the tubulin is polymerized into microtubules extending from the membrane [72]. If the microtubule system in the cells is destroyed by nocodazole and cool ing, then at early stages of recovery (nocodazole wash out and warming) the microtubules can be seen growing directly from vesicles containing Golgi markers [73]. Several proteins are involved in the process of γ tubulin recruitment to the Golgi: GMAP210 -golgin of cis Golgi [78]; CG NAP (AKAP450, yotiao) -a long fibril lar protein, acceptor of protein kinase A [79,80]; p115 [81]; myomegalin -a protein similar to AKAP450 [82]; CDK5RAP2 protein [83].…”
mentioning
confidence: 99%